Analisis Penerapan Sistem Proteksi Kebakaran Aktif Dalam Upaya Pencegahan dan Penanggulangan Bahaya Kebakaran - Maisyah Ardila; Raspiyahni Raspiyahni; Regita Cahyani; Abdurrozzaq Hasibuan (PT. Alahyan Publisher Sukabumi, 2024)
Fire is a serious threat that can cause significant material loss and loss of life. To overcome this threat, implementing an active fire protection system is very important in efforts to prevent and control fires. This research aims to analyze the application of active fire protection systems through literature studies. This study also evaluates the effectiveness of the protection system in responding to fire incidents. The research results show that there are two fire protection systems, namely an active protection system and a passive protection system. An active fire protection system can provide early warning and start the extinguishing process quickly, thereby reducing the negative impact of fires. With a deeper understanding of these aspects, it is hoped that more effective solutions can be obtained in protecting assets and human lives from the dangers of fire.